A Household Survey on Awareness of Hiv/Aids Among Rural People of Chandbela Vdc Of Eastern Nepal - Khanal, Vijay Kumar; Thapa, Bijay; Rayamajhi, Rajan Bikram; Adhikari, Puspanjali; Budhathoki, Shyam Sundar; Ghimire, Anup; Singh, Suman Bahadur; Pokharel, Paras Kumar (Journal of Nobel Medical College, 2015)
Background: In the past 20 years HIV/AIDS has become an increasing global phenomenon. The rising trend of morbidity and mortality has not only changed the demography but also poses a huge socio-economic burden on well-being of households, communities and country. In Nepal as the epidemic is maturing. However, the epidemic has never been maintained in the general population through heterosexual transmission in Nepal, rather it is driven by the infections among higher risk populations and their sexual partners. Objectives: To assess the knowledge about HIV/AIDS among household level. Material and Methods: A household based survey was conducted in all the nine wards of Chandbela VDC. Interview was conducted using pre-tested semi structured questionnaire which included socio demographic profile and characteristics to assess awareness on HIV/AIDS. The data was analyzed to calculate percentages and proportions. Results: Out of total population (7034), 50.39% were male and 49.60% were female. Majority of the males and females were literate i.e. 73.58% and 51.37% respectively. Out of 1274 households, 946(74.25%) households were below poverty line, where 19.34% of people did agriculture for living and 3.3% were migrant worker. Most of the people 73.2% were aware and had heard about HIV/AIDS from various medium like 24.53% from radio, 15.19% from friends However, 16.8% of the people never heard of HIV/AIDS. According to 33% of people unsafe sexual practice could transmit HIV/AIDS and 28.83% of people thought avoiding unsafe sexual Practice can prevent from acquiring HIV/AIDS. Of the total respondents, 61.6% of the people believed that even a healthy looking person can have HIV/AIDS. Attitude towards HIV/AIDS patients of majority of population (55.93%) was to avoid any kind of relation or contact with patient. Conclusion: Although majority of the population were literate, were aware of and had heard about HIV/AIDS, the attitude towards the patient was not positive. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.12235 Journal of Nobel Medical College Vol. 3, No.1 Issue 6, 2014, Page: 35-39